Nonvolatile Memory: Ultrafast Multilevel Switching in Au/YIG/n‐Si RRAM (Adv. Electron. Mater. 2/2019). (8th February 2019) - Chen, Zhiwei; Huang, Weichuan; Zhao, Wenbo; Hou, Chuangming; Ma, Chao; Liu, Chuanchuan; Sun, Haoyang; Yin, Yuewei; Li, Xiaoguang
Abstract : Sub‐nanosecond (≈540 ps) resistive switching with high off/on resistance ratio is demonstrated in an Au/YIG/n‐Si resistive random access memory (RRAM) at room temperature and 85 °C in article number1800418 by Yuewei Yin, Xiaoguang Li, and co‐workers. Five discrete resistance levels with ultrafast switching clearly show reliable retentions. Such an RRAM is promising for next‐generation non‐volatile memories with ultrahigh speed, low power consumption, and high density.